Developing the evidence for kinesiology-style manual muscle testing: A series of diagnostic test accuracy studies - Jensen, A; Stevens, R; Burls, A (Elsevier, 2014)
Introduction :Kinesiology-style Manual Muscle Testing (kMMT) is estimated to be practiced by over 1 million people worldwide. Despite its prevalence, the clinical validity of kMMT has never been rigorously assessed and its usefulness is frequently questioned.